Cerebral sodium (23Na) magnetic resonance imaging in patients with migraine: a case-control study - Meyer, Melissa; Schmidt, Alexander; Benrath, Justus; Konstandin, Simon; Pilz, Lothar R.; Harrington, Michael G.; Budjan, Johannes; Meyer, Mathias; Schad, Lothar R.; Schönberg, Stefan; Haneder, Stefan (European radiology, 2019)
Evaluation of MRI-derived cerebral 23Na concentrations in patients with migraine in comparison with healthy controls. Materials and methods. In this case-control study, 24 female migraine patients (mean age, 34 ± 11 years) were enrolled after evaluation of standardized questionnaires. Half (n = 12) of the cohort suffered from migraine, the other half was impaired by both migraine and tension-type headaches (TTH). The combined patient cohort was matched to 12 healthy female controls (mean age, 34 ± 11 years). All participants underwent a cerebral 23Na-magnetic resonance imaging examination at 3.0 T, which included a T1w MP-RAGE sequence and a 3D density-adapted, radial gradient echo sequence for 23Na imaging. Circular regions of interests were placed in predetermined anatomic regions: cerebrospinal fluid (CSF), gray and white matter, brain stem, and cerebellum. External 23Na reference phantoms were used to calculate the total 23Na tissue concentrations. Pearson’s correlation, Kendall Tau, and Wilcoxon rank sum test were used for statistical analysis. Results: 23Na concentrations of all patients in the CSF were significantly higher than in healthy controls (p < 0.001). The CSF of both the migraine and mixed migraine/TTH group showed significantly increased sodium concentrations compared to the control group (p = 0.007 and p < 0.001). Within the patient cohort, a positive correlation between pain level and TSC in the CSF (r = 0.62) could be observed. Conclusion: MRI-derived cerebral 23Na concentrations in the CSF of migraine patients were found to be statistically significantly higher than in healthy controls.
Gesehen am 19.02.2020